The Impact of Social Media Marketing and Online Customer Reviews on the Performance of Small and Medium Enterprises in Malang City - Awur Kuereng, Ruk Elijah; Rachmi, Asminah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This paper is an empirical investigation to determine the impact of Social Media Marketing (SMM) and Online Customer Reviews (OCR) on the performance in Small and Medium Enterprises (SMEs) in Malang City, Indonesia. SME respondents are selected via purposive sampling method of 100 respondents, and data collection procedure is conducted through structured questionnaires followed by their analysis using SPSS 27. The results indicate that social media marketing and online customer reviews are the important tools positively affecting the SME performances related to brand visibility, customer interaction, and trust. The research affirms that proper utilization of Instagram, TikTok, Google Reviews, and TripAdvisor will help acquire more customers and increase revenue. These findings support the theoretical implication of Registered Behavior Technician (RBT) and extend new practical knowledge on how SMEs in the developing countries can take advantage of digital platforms. The newness is that it brings together both Social Media Marketing and the Online Customer Review aspects in measuring their combined effect on the performance of SMEs in a highly dynamic digital economy